Kariuomenės pirmūnų sąjungos įkūrimas ir veikla 1937-1940 metais - Jurevičiūtė, Aušra (Lietuvos istorijos studijos, 2007)
Military Achievers Union was an organization of former soldiers. The establishment of the union was quite late as at the beginning of the First World War in 1914, large numbers of Lithuanians as Russian officials were already serving in the Russian army. When Germany occupied Lithuania in 1915, due to the early mobilization and call-up, about 30,000 Lithuanian soldiers were serving in all Russian fronts from Riga Bay to Caucasus.The national movement of Lithuanians in Russia started after the revolution of the 23rd February (8th March) 1917 which awaked the nations ruled by Russia to strive for their lost independence. Soldiers also participated in the movement. They wanted to be distinguished from the Russian army, to create their national organizations and military units and to support the political struggle for independence of their nations. The movement of Lithuanian soldiers started in separate military unions. On the 25th May, a meeting of 88 delegates representing 16,000 organized soldiers was held in Petrograd. As an outcome of the meeting, the Lithuanian Soldiers Union was established. The aim of the union was to fight for the independence of Lithuania. The union had 8,000 members, 200 of which were officers. The national movement of Lithuanian soldiers involved: 1,238 soldiers and 53 officers of Vitebsk battalion, 1,000 soldiers and 37 officers of Smolensk battalion, 700 soldiers and 27 officers of Rovno battalion, 416 soldiers and 13 officers of Siberia battalion, 200 soldiers, 1 officer and 3 sergeants serving as officers of Valkas cavalry division, 150 soldiers and 21 doctors in Ungėnai. All listed units encompassed 4,000 soldiers ready to return to Lithuania and protect the independence of the native country. Similar organizations were created in Poland and Czechoslovakia.The idea to establish the Military Achievers Union came in 1937, commemorating the 20th anniversary of the national movement in Russia. During the meeting of the participants of the national movement, a committee of 25 persons responsible for the establishment of the union was elected. The aim of the Military Achievers Union was to unite achievers to gather historical and museum material about their activities in Russia, to publish books, to cooperate with other organizations and to ensure the moral and material welfare of the members. However, some of the set tasks were not realized. During the period of 2 years, the organization released and legally registered a medal for the members, which was not presented because of the Soviet occupation.Military Achievers Union had more than 1,200 members and candidates, some of which held important positions in military and state service. 200 volunteer founders of the union were presented with the medal of Volunteer founders, whereas 50 persons were awarded with the Vytis cross. Military Achievers Union did not have enough time to become an active participant in political and social life as it was concerned with organizational works and establishment of new units. However, an assumption can be made that the organization could have become active as it had the intellectual potential. The suggestion is supported by the successful meeting of the 7th-8th September 1937, in Kaunas. The participants of the meeting were the top representatives of the government, the army and society. Good organization, appropriate evaluation of the situation and possibilities made it possible to pass the necessary bill in Seimas. In comparison, other organizations of former soldiers could pass the bills in the course of several years, whereas the volunteers waited for the perquisites for 13 years. The organizational competence of Military Achievers Union was evident in establishing units in towns of Lithuania: from the 31st December 1937 up to the 15th June 1940, 24 new units were founded.